Evidence that the Campylobacter fetus sap Locus Is an Ancient Genomic Constituent with Origins before Mammals and Reptiles Diverged - Tu, Zheng-Chao (American Society for Microbiology, 2001)
Campylobacter fetus bacteria, isolated from both mammals and reptiles, may be either subsp. fetus or subsp. venerealis and either serotype A or serotype B. Surface layer proteins, expressed and secreted by genes in the sap locus, play an important role in C. fetus virulence. To assess whether the sap locus represents a pathogenicity island and to gain further insights into C. fetus evolution, we examined several C. fetus genes in 18 isolates. All of the isolates had 5 to 9 sapA or sapB homologs. One strain (85-387) possessed both sapA and sapB homologs, suggesting a recombinational event in the sap locus between sapA and sapB strains. When we amplified and analyzed nucleotide sequences from portions of housekeeping gene recA (501 bp) and sapD (450 bp), a part of the 6-kb sap invertible element, the phylogenies of the genes were highly parallel. Among the 15 isolates from mammals, serotype A and serotype B strains generally had consistent positions. The fact that the serotype A C. fetus subsp. fetus and subsp. venerealis strains were on the same branch suggests that their differentiation occurred after the type A-type B split. Isolates from mammals and reptiles formed two distinct tight phylogenetic clusters that were well separated. Sequence analysis of 16S rRNA showed that the reptile strains form a distinct phylotype between mammalian C. fetus and Campylobacter hyointestinalis. The phylogenies and sequence results showing that sapD and recA have similar G + C contents and substitution rates suggest that the sap locus is not a pathogenicity island but rather is an ancient constituent of the C. fetus genome, integral to its biology.